Translation in Forming Musical Discourse: A Case Study of English-Language Song Lyrics in Russia - Aleshinskaya, Evgeniya V. (Research in Language, 2020)
The paper considers translation as an intermediate stage in the creation of English-language song lyrics by native Russian speakers. Russian songwriters quite often rely on their native language and translate their thoughts from Russian into English. This leads to the use of a “russified” variety of English, which performs poetic and pragmatic functions and serves as a medium harmonizing content, sound, and music. Drawing evidence from 214 songs in various musical genres, as well as 10 ethnographic interviews with Russian songwriters, it examines the specific features of the Russian variety of English used in song lyrics, and discusses the main views on the authenticity of translation in song lyrics depending on the musical genre.